PENGARUH PEMBERIAN JUS BUAH NAGA (Hylocereus Polyrhizus) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA PENDERITA HIPERGLIKEMIA DI DESA GEMPOL SARI RT 007 RW 003 Kec. SEPATAN TIMUR - Melati Indah Sapitri; Siti Cholifah S; Ida Faridah (Nusantara Hasana Berdikari, 2021)
Hyperglycemia is a condition where the glucose content in the blood is indicated to be excessive. Hyperglycemia, if left unchecked, can lead to diabetes mellitus. The purpose of this study was to determine the effect of giving dragon fruit juice on reducing blood glucose levels in people with hyperglycemia in Gempol Sari Village, rt 007 rw 003 kec. east coast. The type of research used is quantitative with aresearch method quasi-experimental and a non-equivalent control group design. This study begins with the selection of respondents who meet the inclusion criteria. The study was divided into two groups, namely the intervention group 15 respondents and the control group 15 respondents. The data were analyzed using the Wilcoxon signed ranks test. Based on the test results Wilcoxon signed ranks test produces p value (0.001) <α (0.05), then Ho is rejected means that there is the effect of dragon fruit juice to decrease blood glucose levels in patients with hyperglycemia. There is an effect of giving dragon fruit juice (Hylocereus polyrhizus) to decrease blood glucose levels in hyperglycemic patients in Gempol Sari village rt 007 rw 003 kec. east coast.